ANALISIS PENDAPATAN BERSIH DAN EFISIENSI BIAYA USAHATANI PADI SAWAH PADA SISTEM TANAM JAJAR LEGOWO 2:1 DAN 4:1 - Dinar; Umyati, Sri; Kodori, Wiwi; Marina, Ida; Sukmawati, Dety (Journal of Innovation and Research in Agriculture, 2025)
Lowland rice is a major food commodity in Indonesia that plays a crucial role in national food security. The implementation of the jajar legowo planting system is one of the cultivation innovations aimed at increasing productivity and farming efficiency. However, differences in jajar legowo planting patterns may result in variations in production costs and farmers’ income. This study aimed to analyze net income and cost efficiency of lowland rice farming under 2:1 and 4:1 jajar legowo planting systems. The research was conducted in Sindangkerta Village, Indramayu Regency, using a survey method involving rice farmers who applied the 2:1 and 4:1 jajar legowo systems. Primary and secondary data were analyzed quantitatively by calculating production costs, revenues, net income, and cost efficiency using the revenue–cost (R/C) ratio. The results showed that the 2:1 jajar legowo planting system generated higher net income than the 4:1 system. In addition, the R/C ratio values of both planting systems were greater than one, indicating that lowland rice farming under both systems is economically feasible. Therefore, the 2:1 jajar legowo planting system is more cost-efficient and provides higher economic benefits for farmers compared to the 4:1 system..